Development of Agriculture in Turkey and Changing Dynamics: Factor Analysis Approach - ÇELEBİ, HASAN HÜSEYİN; Paksoy, Ayşe (Springer Science and Business Media Deutschland GmbH, 2025)
This study investigates the factors affecting agricultural productivity in Turkey from 1990 to 2023 using factor analysis. As the global population increases, understanding the variables that influence crop yields becomes crucial for sustaining the food supply. The research examines data such as average temperature, rainfall, inflation rates, and fuel prices, sourced primarily from the Turkish Statistical Institute. By applying factor analysis, the study groups these variables into meaningful clusters that reveal the underlying correlations between them and agricultural outputs like wheat, barley, rice, and corn. The results indicate that certain economic and environmental factors, such as consumer inflation and annual average temperature, consistently influence multiple crops. This research contributes a new perspective to the literature by identifying the key factors that drive agricultural productivity in Turkey, providing insights that can inform future agricultural policies. The study concludes with suggestions for further analysis involving a broader range of variables to enhance understanding of the complex dynamics in Turkish agriculture.
International Symposium for Production Research
Part of the book series: Lecture Notes in Mechanical Engineering ((LNME)).
Keywords: Agriculture; Data analysis; Factor analysis; Turkey; Wheat